EndoART: A proposed randomized controlled trial on endometriomas in assisted reproductive technologies, comparing the effect of no intervention, surgery, and prolonged GnRH downregulation on pregnancy rates. Issue 3 (September 2018) - Tomassetti, Carla; Adamson, David; Arici, Aydin; Canis, Michel; Hompes, Peter; Hummelshoj, Lone; Mol, Ben-Willem; Nardo, Luciano; Rombauts, Luk; D'Hooghe, Thomas
Background: Clinical management of endometriomas, prior to starting treatment with assisted reproductive technologies (ART), has since long been a matter of debate. Whereas cystectomy has been advocated in the past, recently more evidence has emerged on the potential negative effect of surgery on ovarian reserve. Parallel to this, prolonged downregulation with GnRH-a (gonadotropin-releasing hormone agonists) has been described to improve ART pregnancy rates in women with endometriosis. However, none of these strategies have been assessed in a large randomized controlled trial. The aim of the EndoART study is to assess whether ovarian surgery or prolonged GnRH-a downregulation result in higher pregnancy rates after ART compared to no intervention in women with endometrioma(s). Methods/design: A parallel randomized multi-center trial has been designed to compare ART pregnancy rates in three different treatment groups: no intervention, ovarian surgery, and prolonged hormonal suppression by GnRH-a prior to ART. The primary outcome measure studied is the clinical pregnancy rate with fetal heart-beat within 6 months after initiation of a fresh ART cycle. Secondary outcome measures studied include live birth rate after one initiated fresh ART cycle, cumulative clinical pregnancy rate with fetal heart-beat and live birth rates (after one fully completed ART cycle: initiated fresh + eventual associated frozen embryo transfer cycles), ART–specific data (e.g. number of oocytes, number of good quality embryos), complications, pelvic pain, and quality of life. Conclusion: This trial may answer the most frequently asked questions by both women with endometriosis and physicians: how do you treat endometrioma in women prior to treatment with ART?